Search of potential antidiabetic drugs in range of 5-(phenoxymethylene)-4-R-1,2,4-triazole-3-thions - Yu. M. Kucheryavyi (Zaporozhye State Medical University, 2016)
The modern pharmaceutical market has countless number of hypoglycemic drugs. But information about domestic antidiabetic drugs based on 1,2,4-triazole nucleus is almost unknown. Researches in this field of science are an important task for scientists of synthetic and organic chemistry. Aim. That's why the purpose of our work is the search for potential hypoglycemic drugs among 3-thioderivatives of 5-(phenoxymethylene)-4-R-1,2,4-triazoles-3-thiones (R=C2H5, C6H5) using screening method and next detailed pharmacological study of the most promising compounds. Methods and methods. Hypoglycemic effect of 1,2,4-triazole derivatives has been evaluated using intraperitoneal glucose tolerance test (IPGTT), which has been reproduced by glucose administering to animals at a dose of 2 g/kg of rat body weight. The glucose level has been determined in blood after 30 minutes. Determination was carried out with the glucose oxidase method using the express analyzer «Accu-Chek Active». The hypoglycemic effect has been studied for active substances using alloxan induced diabetes, which has been reproduced on white nonlinear rats. The alloxan induced diabetes was modeled with intraperitoneal administration of alloxan monohydrate solution at a dose of 75 mg/kg in a 5% citrate buffer solution (pH 4.5), after the 24 h of food deprivation (with free access to water). Results. The research results have been processed with modern statistical analysis methods on PC using the standard package of Microsoft Office 2010 software (Microsoft Excel) and «STATISTICA® for Windows 6.0». A number of compounds which can decrease the level of glucose have been identified based on result of IPGTT. We have established the dependence of the hypoglycemic effect on the chemical structure. Conclusions. The median effective dose has been calculated for most active compound with probit analysis.